In-Service Teachers’ Perceived Measures for Enriching the Teaching of Senior Secondary School History In Kwara State - Hakeem Nafiu; Abubakar Saidu (International Journal of Instructional Technology and Educational Studies)
The teaching of History in senior secondary schools plays a crucial role in shaping students’ understanding of their cultural heritage and societal development. In Kwara State, Nigeria, teachers face unique challenges that can impact the effectiveness of History teaching. Therefore, this research examined the in-service teachers’ perceived measures for enriching the teaching of senior secondary school History in Kwara State. Differences in in-service teachers’ perceptions on the basis of gender and school type were also examined. This study made use of descriptive survey method. The population for the study was all senior secondary school in-service History teachers in Kwara State while the target population was all the senior secondary school in-service History teachers in Ilorin, Kwara State. One hundred and twenty (120) in-service History teachers were sampled for the study using purposive sampling technique. A researcher’ self-developed questionnaire was used for data collection while the data collected for this study were analysed using mean rating to answer the research question while independent t-test was used to test the hypotheses postulated for this study at 0.05 level of significance. Findings from this study revealed that in-service History teachers perceived: using multiple learner-centered methods and resources in conveying contents of History; using field trips and historical places which facilitate teaching and learning of History among others are measures for enriching the teaching of Senior Secondary School History. It was then recommended among others that teachers should make use of multiple learner-centred methods and varieties of instructional approaches in conveying contents of History